Penerapan Morfologi Bahasa Arab dalam Bahasa Indonesia: Studi Kasus di MI Nidhamiyah Ketompen Pajarakan - Latifatul Hasanah; Ainur Rofiq Sofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to analyze the morphological forms of Arabic applied in the Indonesian language within the learning context at MI Nidhamiyah, Ketompen Village, Pajarakan District, Probolinggo Regency. A qualitative approach with a descriptive method was employed. The research subjects consisted of Arabic language teachers and students learning Arabic morphology at the institution. Data were collected through direct observation, semi-structured interviews, and documentation, including student writings, textbooks, and learning notes. Data analysis was carried out through stages of data reduction, data display, and conclusion drawing. To ensure data validity, triangulation techniques were applied. The results of the study indicate that the integration of Arabic morphology into the Indonesian language has a positive impact on students' understanding of word forms and meanings related to morphological structures. This research is expected to contribute to the development of Arabic language instruction at the elementary education level.